Two new eudesmanolides from sphaeranthus indicus (Linn) - Jadhav, Ravindra B.; Sonawane, Kiran B.; Deshpande, Nirmala R.; Rojatkar, Supada R. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2007)
Two new eudesmanolides have been isolated from the aerial part of Sphaeranthus indicus and their structures have been established as 11 alpha,13-dihydro-3 alpha,7 alpha-dihydroxyeudesm-4-en 6 alpha, 12-olide 1, 4-en-6 beta,7 alpha-eudesmanolide 3, on the basis of spectral data and comparison of spectral data with those of reported data of compounds 2, 4 and 5.
Keywords: eudesmanolides; olide; Sphaeranthus indicus

Phytochemical investigation of artemisia pallens - Ruikar, Anjali D.; Jadhav, Ravindra B.; Phalgune, Usha D.; Rojatkar, Supada R.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Helvetica Chimica Acta, 2011)
Two new eudesmanolides, pallensin (1) and 4-epipallensin (2), along with a known eudesmanolide, santonin, and a known flavone, 4-epivalgarin, have been isolated from the aerial part of A. pallens. Their structures were established by detailed spectral studies (1D and 2D) and by comparison of their spectroscopic data with those of known compounds.

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure